Secondary Metabolites of Plants as Modulators of Endothelium Functions - Bartáková, Anna; Nováková, Marie (International journal of molecular sciences, 2021)
According to the World Health Organization, cardiovascular diseases are the main cause of death worldwide. They may be caused by various factors or combinations of factors. Frequently, endothelial dysfunction is involved in either development of the disorder or results from it. On the other hand, the endothelium may be disordered for other reasons, e.g., due to infection, such as COVID-19. The understanding of the role and significance of the endothelium in the body has changed significantly over time-from a simple physical barrier to a complex system encompassing local and systemic regulation of numerous processes in the body. Endothelium disorders may arise from impairment of one or more signaling pathways affecting dilator or constrictor activity, including nitric oxide-cyclic guanosine monophosphate activation, prostacyclin-cyclic adenosine monophosphate activation, phosphodiesterase inhibition, and potassium channel activation or intracellular calcium level inhibition. In this review, plants are summarized as sources of biologically active substances affecting the endothelium. This paper compares individual substances and mechanisms that are known to affect the endothelium, and which subsequently may cause the development of cardiovascular disorders.
Keywords: Plants; vazodilatace; Plant Extracts; Humans; Endothelium, Vascular; Vasodilation; nitric oxide; vazodilatancia; cévní endotel; vasoconstriction; lidé; vasodilation; rostlinné extrakty; sekundární metabolismus; vasoactive substances; Vasodilator Agents; Secondary Metabolism; endothelium; rostliny